Smart Polymer Nanocomposites: Biomedical and Environmental Applications - Bhawani, Showkat Ahmad (Woodhead Publishing, 2021)
Smart Polymer Nanocomposites: Biomedical and Environmental Applications presents the latest information on smart polymers and their promising application in various fields, including their role in delivery systems for drugs, tissue engineering scaffolds, cell culture sports, bioseparation, and sensors or actuator systems.